2020
DOI: 10.3390/nano10071280
|View full text |Cite
|
Sign up to set email alerts
|

Direct As(V) Determination Using Screen-Printed Electrodes Modified with Silver Nanoparticles

Abstract: Carbon-nanofiber-based screen-printed electrodes modified with silver nanoparticles (Ag-NP-SPCNFEs) were tested in a pioneering manner for the direct determination of As(V) at low μg L−1 levels by means of differential pulse anodic stripping voltammetry. Screen-printed electrodes were modified with two different types of Ag-NPs, nanoseeds (NS), and nanoprisms (NPr) and characterized both microscopically and electrochemically. Furthermore, after optimizing the direct voltammetric determination of As(V),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, triangular-shaped nanoparticles were synthesized for the voltammetric determination of heavy metal ions. Torres-Rivero et al [ 5 , 42 ] synthesized silver nanoparticles (Ag-nanoseeds and Ag-nanoprisms) by the seed mediated approach [ 84 , 85 ]. SEM and TEM images showed that the Ag-nanoprisms had triangular morphology with a size between 14.25 and 16.46 nm ( Figure 5 A).…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, triangular-shaped nanoparticles were synthesized for the voltammetric determination of heavy metal ions. Torres-Rivero et al [ 5 , 42 ] synthesized silver nanoparticles (Ag-nanoseeds and Ag-nanoprisms) by the seed mediated approach [ 84 , 85 ]. SEM and TEM images showed that the Ag-nanoprisms had triangular morphology with a size between 14.25 and 16.46 nm ( Figure 5 A).…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
“…In a previous study, the Pb(II) and Cd(II) ions were determined in an acetic acid/acetate buffer [ 5 ]. In contrast, in another investigation, As(V) ions were detected in a HCl electrolyte [ 42 ] using the differential pulse anodic stripping voltammetry technique.…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, electrochemical sensors represent a versatile tool for monitoring different samples in the environmental field. In addition, the literature has reported how modifying their surface with nanomaterials enhanced the electrochemical reactivity and sensitivity to specific analytes [9], allowing lower detection limits and higher sensitivity for stripping techniques [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This limits the applicable electrode materials, and a carbonbased electrode is not applicable because of its low electrocatalytic activity. Therefore, many researchers have recently focused on the exploration of highly electrocatalytic metal nanomaterials including gold nanoparticles, (4)(5)(6)(7)(8) platinum nanoparticles, (9) silver nanoparticles, (10) cobalt oxide nanoparticles, (11) and nanostructured MnO x . (12) Among them, Au is known to have higher affinity to As(III) deposition and stripping.…”
Section: Introductionmentioning
confidence: 99%